Reinterpretation of Halal Tourism Hadith in DSN-MUI Fatwa No. 108 of 2016 - afif, Muhammad; Su’aidi, Hasan; Marwan bin Mohammad Amin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The focus of this paper is on the quality and understanding of the hadith in the DSN-MUI Fatwa No. 108 of 2016 concerning halal tourism. The use of hadith as a source of fatwas is important, especially with regard to the legality of an Islamic perspective. However, like a fatwa, this hadith is not followed by an explanation regarding the quality of the hadith and how to understand the meaning that comes from the hadith so that it can be used as a source of fatwa. On the one hand, it must be ensured that the hadith can be accounted for as originating in the Prophet, both in sanad and matan so that its use has high validity. In addition, the existence of hadith when it was born has a distance in time and space that is quite far so whether reinterpretation is needed or not. To answer the problem, this study uses library research by applying the method of criticizing sanad, matan and ma'anil hadith. In the data analysis using descriptive-analytical techniques. This paper shows that there are two hadiths used by DSN-MUI. The first hadith narrated by Imam Ahmad bin Hanbal is of da'if quality because there are two narrators who are considered weak, namely Ibn Lahi'ah and Darraj bin Sam'an. Meanwhile, the second hadith, which was narrated by Imam al-Bukhari and Imam Muslim, is of valid quality. The content of the meanings of the two hadiths used by the DSN-MUI is a recommendation for travel that is not only aimed at entertainment or a healthy body, but also travel compassion and increase obedience.